Evaluation of a new enzyme‐linked immunosorbent assay (ELISA) in the diagnosis of rhinovirus infection - Al‐Nakib, W. (J Med Virol, 2005)
This study describes the evaluation of a newly developed ELISA for the direct detection of rhinovirus antigens in nasal washings. Of 54 volunteers inoculated with 100 TCID(50) of human rhinovirus type 2 (HRV‐2), 50 (96.6%) and 32 (59%) excreted antigen and virus on at least 1 of 3 days investigated, respectively. Thirty‐three (61%) had significant rises in rhinovirus‐specific IgA by ELISA. Twelve (22%) developed symptoms of colds. Generally the ELISA detected antigen more frequently in volunteers later in the course of infection and provided evidence of infection in a higher proportion of asymptomatic compared with symptomatic volunteers. On the other hand, virus isolation detected virus more frequently earlier in the course of infection and in a higher proportion of symptomatic compared with asymptomatic volunteers. We conclude that rhinovirus antigen detection by ELISA is a simple, rapid, sensitive, and practical test to diagnose a rhinovirus infection and potentially a viable alternative to virus isolation.